Sugar content in liquid oral medicines for children - Peres, Karen Glazer; Oliveira, Caroline Teixeira; Peres, Marco Aurélio; Raymundo, Melissa dos Santos; Fett, Roseane (Revista de Saúde Pública, 2005)
The most sold and/or prescribed liquid oral medicines for children in Tubarão, Southern Brazil, were assessed. Their sugar concentration was tested and compared to those in their directions for use. All pharmacies and pediatricians working in the city were visited by a previously trained interviewer. Pre-tested questionnaires were applied in order to assess the most sold pediatric as well as the most prescribed pediatric liquid oral medicines. Three samples of each medicine were analyzed by Lane-Eynon general volumetric method. Among the 14 most sold/prescribed medicines only four did not have sugar contents (analgesic, cortisone, and syrups). Sugar concentration ranged from 8.59 g/100 g of drug (SD=0.29 g/100 g) to 67.0 g/100 g of drug (SD=6.07 g/100 g). Only 50.0% of the total medicines that presented sugar in their ingredients showed this information in their directions.